1998
DOI: 10.1007/s000240050153
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional Crustal Velocity Structure along Hirapur-Mandla Profile from Seismic Refraction and Wide-angle Reflection Data

Abstract: The seismic velocity structure of the upper and lower crusts along Hirapur-Mandla profile was obtained by 2-D forward modeling of the refraction and wide-angle reflection data. Digitized record sections of the analog data were utilized for delineation of the crustal velocity model across the Vindhyan basin and the Narmada-Son lineament by travel-time modeling and qualitatively matching the amplitudes of synthetic seismograms with seismic record sections. An interface at a depth of 8 km has been traced from wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…These results were based on the modeling of travel-time data only. MURTY et al (1998) derived the first 2-D crustal seismic velocity model by considering the travel-time modeling and amplitude analysis utilizing the digitized record sections. In that paper, we have modeled only the long and continuous wideangle reflection phases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results were based on the modeling of travel-time data only. MURTY et al (1998) derived the first 2-D crustal seismic velocity model by considering the travel-time modeling and amplitude analysis utilizing the digitized record sections. In that paper, we have modeled only the long and continuous wideangle reflection phases.…”
Section: Introductionmentioning
confidence: 99%
“…1). The interpreted velocity boundaries have then been extended to propose a density model along this profile for a better constrained interpretation and as an update to the 2-D velocity model presented earlier (MURTY et al, 1998). The present study forms a part of the integrated geophysical modeling of the Narmada region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pleistocene sedimentary terraces in SNF zone are tilted 20-25 ∘ in the tract Hardi-Jabalpur and are also displaced 10-15 m near Navagram [15]. The seismic structure and existence of sedimentary basin of SONATA zone is interpreted by Murty et al [16] and Kumar et al [17] using 2D crustal seismic velocity models and 2D gravity modeling by Mishra, [18], Verma and Banerjee [19], Sridhar and Tewari, [20] and Mishra et al [21]. The high Bouguer gravity anomaly between Jabalpur and Mandla suggests localized uplift of SNSF and the presence of a magmatic body at different depths.…”
Section: Introductionmentioning
confidence: 99%
“…The high Bouguer gravity anomaly between Jabalpur and Mandla suggests localized uplift of SNSF and the presence of a magmatic body at different depths. Murty et al [16] have concluded that the upper Vindhyans directly overlie the Archaean basement between Hirapur and Narsinghgarh. Between Narsinghgarh and Katangi, the Vindhyan basin consists of the upper and lower Vindhyans [22].…”
Section: Introductionmentioning
confidence: 99%